Antimicrobial and Antiviral Properties of Metal Nanoparticles and Their Potential Use in Textiles: A Review - Nonsikelelo Sheron, Mpofu; Mwasiagi, Josphat Igadwa; Nganyi, Eric Oyondi; Kamalha, Edwin (University of Oradea Fascicle of Textiles, Leatherwork, 2021)
Recent global trends have put an emphasis on the importance of hygiene in all sectors including textiles. Antimicrobial and antiviral finishes are used in textiles to control bacteria, moulds, fungi and viruses on the textile substrate. Metal nanoparticles have been shown to posess antimicrobial and antiviral properties and can potentially be used in textiles for the production of fabrics with these functions. The aim of this paper is to explore the different antimicrobial and antiviral properties possessed by zinc oxide nanoparticles, titanium dioxide nanoparticles, silver nanoparticles and copper nanoparticles and their potential use in textiles. The challenges associated with these metal nanoparticles have also been assessed. Most of the metal nanoparticles studied display antibacterial properties against gram-negative Escherichia Coli and Pseudomonas Aeruginosa as well as gram-positive Staphylococcus aureus. Antiviral activities were also observed against Herpes Simplex Virus Type 1 (HSV-1), H1N1 influenza, poliovirus and foot and mouth disease. Although the metal nanoparticles showed potential for use as antimicrobial and antiviral finishes for textile substrates, environmental concerns have been raised on their use as they tend to be toxic during use and also produce a harmful washing effluent. Future studies should focus on the mitigation of the toxicity challenges associated with the use of metal nanoparticles.
Keywords: Nanoparticles; Antimicrobial activity; Antiviral activity; Silver nanoparticles; Zinc Oxide nanoparticles